2013
DOI: 10.1167/iovs.13-11859
|View full text |Cite
|
Sign up to set email alerts
|

Elevation of Conjunctival Epithelial CD45INTCD11b+CD16+CD14Neutrophils in Ocular Stevens-Johnson Syndrome and Toxic Epidermal Necrolysis

Abstract: These data highlight that a neutrophilic infiltrate is present in mildly inflamed or clinically quiescent conjunctival mucosa in patients with ocular SJS-TEN, where neutrophil numbers inversely correlate with disease duration. Neutrophil persistence endorses the hypothesis of an unresolved innate-inflammatory process that might account for disease progression.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
22
0
1

Year Published

2015
2015
2025
2025

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(25 citation statements)
references
References 37 publications
(43 reference statements)
2
22
0
1
Order By: Relevance
“…Our results confirm a solid increase in granulocytes in inflamed eyes, as reported by Williams et al, 22 although CD45 bright cells were significantly reduced. The percentages of monocytes and T lymphocytes were not significantly different between the two groups, although monocytes were most represented in inflamed eyes and T lymphocytes in noninflamed eyes.…”
Section: Figuresupporting
confidence: 93%
“…Our results confirm a solid increase in granulocytes in inflamed eyes, as reported by Williams et al, 22 although CD45 bright cells were significantly reduced. The percentages of monocytes and T lymphocytes were not significantly different between the two groups, although monocytes were most represented in inflamed eyes and T lymphocytes in noninflamed eyes.…”
Section: Figuresupporting
confidence: 93%
“…19,20 The distinction between ''acute'' and ''chronic'' ocular complications of SJS/TEN remains blurred; however, some studies have used an arbitrary cut-off of !12 months to define chronicity. 8,21 Although the cutaneous manifestations generally heal without longterm sequelae, severe ocular surface complications may persist long after the systemic condition has subsided. In addition, chronic ocular disease in SJS/TEN tends to be progressive and unpredictable, with poor correlation with the severity of acute ocular complications.…”
Section: Ocular Complications and Categorizationsmentioning
confidence: 99%
“…20,22 Persistent ocular surface inflammation can result in a multitude of long-standing sequelae such as keratoconjunctivitis sicca, ocular surface keratinization, corneal neovascularization, trichiasis/districhiasis, entropion/ectropion, lagophthalmos, extensive subconjunctival fibrosis, and/or symblepharon formation. 18,21,23,24 Sotozono et al reported that the most common chronic ocular manifestations were the loss of the palisades of Vogt (POV) and development of meibomian gland dysfunction. 8 Corneal complications (neovascularization and opacification) are correlated with the worst longterm visual prognosis.…”
Section: Ocular Complications and Categorizationsmentioning
confidence: 99%
See 2 more Smart Citations